2022
DOI: 10.37762/jgmds.9-3.286
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risk of Surgical Site Infection With Open Cholecystectomy Vs Laparoscopic Cholecystectomy

Abstract: OBJECTIVES: This study aimed to compare the risk of surgical site infection with open vs laparoscopic cholecystectomy. METHODOLOGY: This randomized control trial was done at the Department of Surgery, Hayatabad Medical Complex, Peshawar, for 12 months from 11/5/2018 to 11/5/2019. 116 patients were recruited for this study, 58 for each group randomly allocated to a group by lottery method and concealed Allocation. Patients in Group A underwent laparoscopic cholecystectomy, while patients in group B underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Duration of surgery however also did not show any statistically correlation as patients having surgical site infection equally common among both groups. A retrospective study revealed 15.9% prevalence of SSI [17,19,20]. In ours study Surgical site infections were more common after emergency surgeries than after elective ones.…”
Section: Discussionsupporting
confidence: 50%
“…Duration of surgery however also did not show any statistically correlation as patients having surgical site infection equally common among both groups. A retrospective study revealed 15.9% prevalence of SSI [17,19,20]. In ours study Surgical site infections were more common after emergency surgeries than after elective ones.…”
Section: Discussionsupporting
confidence: 50%
“…From 3-20% of the global population suffers from it, according to published studies. [13] Laparoscopic cholecystectomy has surpassed open surgery in frequency of use at most institutions in recent years, becoming a standard surgical procedure. [14] In 94 cases included cases of current study, 47 received open cholecystectomy in group I and 47 cases of group II received open cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] In 94 included cases, 63 (67.02%) were females and 31 (32.98%) were males. [13] Inflammation is caused by changes in the immune system that are triggered by surgical intervention. [17] Posttraumatic immune suppression, in any form, is linked to an increased risk of septic complications.…”
Section: Discussionmentioning
confidence: 99%